1966
DOI: 10.1084/jem.123.6.1013
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Effect of the Microbial Flora on Macrophage Function and the Immune Response

Abstract: The immune response to bacteria and to a soluble protein was compared in germfree and conventionalized mice. Sixty germfree and 59 conventionalized mice received a suspension of killed Serratia marcescens into one front foot-pad and sterile horse ferritin into the other and were sacrificed in groups from 2 hr to 14 days after inoculation. All mice had no pre-existing antibody to either antigen and the flora of the conventionalized mice never contained Serratia. Lymphatic tissue changes and the fate of the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 20 publications
(13 reference statements)
0
22
0
Order By: Relevance
“…Dineen (1961) suggested that this effect could be explained by the stimulation of non-specific defence mechanisms, and it has been shown that the digestive capacity of macrophages from germ-free mice is less than that of cells from conventionally reared animals (Bauer, Paronetto, Burns & (1972). Einheber, 1966). The possibility that migration of bacteria from the gut is necessary for the systemic response is worth considering since it has already been shown that this is a common occurrence in young chicks (Fuller & Jayne-Williams, 1968) and it has been suggested that it might continue undetected throughout life (Fuller & Jayne-Williams, 1970~).…”
Section: ( 5 ) Body Temperaturementioning
confidence: 99%
“…Dineen (1961) suggested that this effect could be explained by the stimulation of non-specific defence mechanisms, and it has been shown that the digestive capacity of macrophages from germ-free mice is less than that of cells from conventionally reared animals (Bauer, Paronetto, Burns & (1972). Einheber, 1966). The possibility that migration of bacteria from the gut is necessary for the systemic response is worth considering since it has already been shown that this is a common occurrence in young chicks (Fuller & Jayne-Williams, 1968) and it has been suggested that it might continue undetected throughout life (Fuller & Jayne-Williams, 1970~).…”
Section: ( 5 ) Body Temperaturementioning
confidence: 99%
“…It has been reported that the immune system in germfree animals are poorly developed compared with those of conventional animals and that antigenic stimulation with some bacteria or other antigenic substances is important for the maturation of the immune system (1,14). This new approach suggests that p.o.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in germfree mice highlight the importance of the gut microbiota to proper immunological development—these animals have reduced numbers of immune cells present in their intestinal lamina propria and smaller Peyer’s patches compared to conventionally reared mice (710). Systemically, they exhibit a diminished capacity for antibody production, fewer plasma cells, smaller mesenteric lymph nodes, and reduced numbers of germinal centers versus their conventional counterparts (11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in germfree mice highlight the importance of the gut microbiota to proper immunological development-these animals have reduced numbers of immune cells present in their intestinal lamina propria and smaller Peyer's patches compared to conventionally reared mice. [7][8][9][10] Systemically, they exhibit a diminished capacity for antibody production, fewer plasma cells, smaller mesenteric lymph nodes, and reduced numbers of germinal centers vs their conventional counterparts. 11 Immune maturation can be induced in germfree mice by colonization with a complex gut microbiota; however, some notable deficits and distinctions remain into adulthood depending upon the age of mice at the time of microbial exposure.…”
mentioning
confidence: 99%